Pembuatan Mi Instan Berbahan Tepung Jagung Lokal Riau Dan Tapioka - Rifka Fitri Isnaini; Usman Pato; Yusmarini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research was to obtain the best rasio of Riau local corn flour and tapioca which meet the Indonesian Quality Standard of instant noodle (SNI 01-3551-2000). Research was carried out experimentally using a Completely Randomized Design (CRD) with 5 treatments and 3 replications in order to obtain 15 experimental units. Treatments of this research were JT0 (100% corn flour) as control treatment, JT1 (75% corn flour : 25% tapioca), JT2 (65% corn flour : 35% tapioca), JT3 (55% corn flour : 45% tapioca) and JT4 (45% corn flour : 55% tapioca). Data obtained were statistically analyzed using Analysis of Variance (ANOVA). If the calculated F is greater than or equal to F table then continued with DNMRT test at 5% level. The result show that addition of tapioca significantly affected the intacness of noodle, moisture content after frying, total acid value, and rehydration time, but did not significantly influence the moisture content after drying and protein content. The best treatment was JT4 with an intacness of 96,96%; moisture content after drying of 7,71%; moisture content after frying of 2,03%; protein content of 2,83%; total acid value of 0,22 and rehydration time of 5,41 minutes.   Keywords: Local Riau corn flour, tapioka flour and instant noodle